OP0129 AUTOREACTIVE, CITRULLINATED PEPTIDE-SPECIFIC T CELLS IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Swift, J.; Stanway, J.; Hilkens, C.; Anderson, A.; Pratt, A.; Isaacs, J.
Abstract : Background: Self-reactive CD4+ T cells are thought to play a key role in the pathogenesis of rheumatoid arthritis (RA) and represent a target for antigen-specific, tolerogenic therapies 1 . Phenotyping such cells could provide the means with which to monitor these treatments. Here, we aimed to demonstrate antigen-induced T cell responses to RA relevant epitopes using peptide stimulation of peripheral blood mononuclear cells (PBMC). Several autoantigens have been described in RA, including various citrullinated peptide (cit-peptide) epitopes 2 ; here we have used a combination of cit-peptides that will be used to load tolerogenic dendritic cells in a forthcoming experimental medicine study (AuToDeCRA II). Objectives: To detect peripheral blood T cell proliferation in response to candidate autoantigens in RA patients and healthy controls (HCs) using flow cytometry. Methods: PBMC from RA patients and HCs were obtained following informed consent and were cryopreserved. Prior to use, cells were thawed in medium supplemented with human serum and were labelled with a proliferation tracking dye (PTD). 2x10 5 labelled cells were plated into 96 well plates with a minimum of 7 replicates per condition and were either cultured alone or stimulated with individual peptides at varying concentrations or a peptide pool. On day 9, cells from replicate wells were harvested, pooled and stained for surface markers and viability. Samples were acquired on a BD Fortessa X20 and analysis was performed in FlowJo version 10. A manual gating strategy was used to identify CD45RO+ (memory) CD4+ T cells and amongst this population, activated/proliferated cells were defined as CD25+ PTD low. Stimulation indices (SI) were calculated as the percentage of activated/proliferated cells from stimulated wells divided by the percentage from unstimulated wells. Results: Ten RA patients (including early and established disease) were recruited alongside seven HCs. Cit-peptides were initially titrated on an individual basis to determine the optimum concentration for use (n = 2). We then compared stimulation with either single peptides or a pool (n = 2), and found that PBMC stimulated with the pooled cit-peptides had a higher proliferative response. Both single and pooled cit-peptide induced T cell proliferation was observed in both RA and HC samples (Figure 1 ); the largest responses were seen amongst RA patients, with a maximum stimulation index of 52.4 compared to a maximum of 6.75 in the HC group. Only 1 HC sample responded with an SI greater than 3.0, whereas 50 % of RA patients elicited responses above this. Two of the RA patients failed to respond to the peptide pool (SI < 1.0). Of note, RA patients were not selected on the basis of tissue type whereas selected peptides bind preferentially to class II HLA containing the shared epitope (SE). Conclusion: In non-HLA typed individuals, cit-peptide induced proliferative T cell responses were detectable in both RA patients and HCs, and although SIs overall were higher amongst RA patients this did not reach statistical significance in this small sample. Not all RA patients responded to the peptide pool which may be due to the limited number of citrullinated epitopes used, or to RA patients with a non-SE HLA type. Additional work should establish the need for HLA typing in this assay; around half of seropositive RA patients would be expected to be SE positive 3 . Furthermore, a wider array of cit-peptides may be needed to demonstrate autoreactivity in a broader cross-section of RA patients. Our future plans are to further phenotype the cellular subsets responding to the peptide pool and to study assay data in the context of clinical outcomes, to assess its utility for immune monitoring. References: [1]McInnes, I. B. & Schett, G. N Engl J Med. 2011; 365(23):2205-2219 [2]James, E. A et al . Arthritis Rheum. 2014; 66(7):1712-1722 [3]Thomson, W et al . Arthritis Rheum. 1999; 42(4):757-762 Disclosure of Interests: Jessica Swift: None declared, James Stanway: None declared, Catharien Hilkens: None declared, Amy Anderson: None declared, Arthur Pratt Grant/research support from: Pfizer, GlaxoSmithKlein, John Isaacs Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, Gilead, Janssen, Merck, Pfizer, Roche